2014
DOI: 10.1075/aral.37.3.02dix
|View full text |Cite
|
Sign up to set email alerts
|

Dodgy data, language invisibility and the implications for social inclusion

Abstract: As part of the ‘Bridging the Language Gap’ project undertaken with 86 State and Catholic schools across Queensland, the language competencies of Indigenous students have been found to be ‘invisible’ in several key and self-reinforcing ways in school system data. A proliferation of inaccurate, illogical and incomplete data exists about students’ home languages and their status as English as an Additional Language/Dialect (EAL/D) learners in schools. This is strongly suggestive of the fact that ‘language’ is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Arguably, practices we have come to recognize as indications of fairness in educational testing such as 'careful standardization of tests and administration conditions' in the Code of Fair Testing Practices in Education (Joint Committee on Testing Practices, 2004) may well be the cause of ill-effect when the context, the educational environment and the test-taker linguistic background differs so markedly from the literacy practices valued by the 'standard language culture' (Milroy, 2001) and on which the construct is modelled. According to Dixon and Angelo (2014), this has resulted in a widespread ignorance of the value of multilingualism or need for English language learning for Indigenous children. In their view, Australia's 'monolingual mindset' (Clyne, 2008; see also Shohamy, 2011) has assisted the safe passage of NAPLAN 'literacy and numeracy testing' into schooling as if it were not in any language and hence fair, even for students who are speakers of Indigenous traditional and contact varieties, with little English proficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably, practices we have come to recognize as indications of fairness in educational testing such as 'careful standardization of tests and administration conditions' in the Code of Fair Testing Practices in Education (Joint Committee on Testing Practices, 2004) may well be the cause of ill-effect when the context, the educational environment and the test-taker linguistic background differs so markedly from the literacy practices valued by the 'standard language culture' (Milroy, 2001) and on which the construct is modelled. According to Dixon and Angelo (2014), this has resulted in a widespread ignorance of the value of multilingualism or need for English language learning for Indigenous children. In their view, Australia's 'monolingual mindset' (Clyne, 2008; see also Shohamy, 2011) has assisted the safe passage of NAPLAN 'literacy and numeracy testing' into schooling as if it were not in any language and hence fair, even for students who are speakers of Indigenous traditional and contact varieties, with little English proficiency.…”
Section: Resultsmentioning
confidence: 99%
“…This monitoring has consistently found that Indigenous children are not achieving at the same level as the rest of the population across all states (Ford, 2013). Angelo (2013) points out that the disaggregation of Indigenous students' scores has made this group 'highly visible' and hence subject to 'intensive educational interventions' on the basis of poor NAPLAN results, but with no recognition in the test data that many Indigenous children are also English language learners (p. 54, see also Dixon & Angelo, 2014).…”
Section: Naplan and The Monitoring Of Indigenous Childrenmentioning
confidence: 99%
“…However, census reports can be inaccurate (e.g.,Morphy(ed. ), 2007;Simpson, 2013;Dixon and Angelo, 2014). My own estimates place speaker numbers at a minimum of 2000.Frontiers in Psychology | www.frontiersin.org…”
mentioning
confidence: 83%
“…Further, students with disabilities may be deprived of the right to NAPLAN participation, and adequate support for additional needs (Cumming & Dickson, 2013). Some scholars argue that NAPLAN has inadequate procedures for inclusion, and further discriminates against high-learning-needs students, by labelling them academic failures (Dixon & Angelo, 2014).…”
Section: Equitymentioning
confidence: 99%